2009
DOI: 10.1007/s00534-009-0167-6
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for hepatocellular carcinoma: Korean experience

Abstract: Hepatocellular carcinoma (HCC) is the second most common cause of male cancer death in Korea, where the major etiology, chronic hepatitis B virus infection, is endemic. With a high incidence of unresectable HCCs and a low cadaveric organ donation rate, the number of adult living-donor liver transplantations (LDLTs) has increased rapidly, by tenfold, over the past 10 years, as an alternative to deceased-donor liver transplantation (DDLT) in Asia, including Korea. Currently, HCC accounts for more than 40% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
(43 reference statements)
0
37
0
Order By: Relevance
“…59 The correlation between PET positivity and poor outcomes after LT has been validated in many studies subsequently. [62][63][64][65][66][67][68] In particular, patients beyond the Milan criteria but with negative PET status could have good overall and recurrence-free survivals comparable to those within the Milan criteria. 65,67 However, PET has not been integrated into candidate selection process for LT for HCC yet.…”
Section: Fluorine-18-flurodeoxyglucose Positron Emission Tomographymentioning
confidence: 99%
“…59 The correlation between PET positivity and poor outcomes after LT has been validated in many studies subsequently. [62][63][64][65][66][67][68] In particular, patients beyond the Milan criteria but with negative PET status could have good overall and recurrence-free survivals comparable to those within the Milan criteria. 65,67 However, PET has not been integrated into candidate selection process for LT for HCC yet.…”
Section: Fluorine-18-flurodeoxyglucose Positron Emission Tomographymentioning
confidence: 99%
“…Kornberg et al (51) reported that tumor uptake of 18 F-FDG on preoperative PET scans is significantly associated with tumor grade as well as with microvascular invasion on explant pathology in recipients with HCC, and Lee et al (52) reported that 18 F-FDG-PET is a significant predictor of tumor recurrence in liver transplantation. NLR, which is a simple index of systemic inflammation, has been reported to be associated with prognosis in patients with various kinds of malignancies, including HCC (53,54).…”
Section: Biomarkers To Predict Biologically Aggressive Hccmentioning
confidence: 99%
“…Thus, in Asia, many LDLT programs accept patients with HCC beyond the Milan criteria for LDLT because they view a living donor organ as a private gift and the reported 3-year survival rates for such patients are higher than 50%. [11][12][13][14] In North America, it is also considered ethically acceptable to use LDLT and DDLT for the treatment of patients with HCC tumors beyond the Milan criteria, particularly when the tumors have been successfully down-staged before transplantation 15 or the recipients do not have unfavorable biological markers such as an alpha-fetoprotein level greater than >1000 ng/mL. 16 The prognosis for patients with HCC with highly unfavorable factors (eg, macroscopic vascular invasion) is very poor, so these patients are poor candidates for either DDLT or LDLT outside clinical trials.…”
Section: Quality Of the Evidence (Cebm Level 2b)mentioning
confidence: 99%
“…16 The prognosis for patients with HCC with highly unfavorable factors (eg, macroscopic vascular invasion) is very poor, so these patients are poor candidates for either DDLT or LDLT outside clinical trials. 11,17,18 Are there reasons to be cautious about preferentially or only offering LDLT for HCC? Yes, there are.…”
Section: Quality Of the Evidence (Cebm Level 2b)mentioning
confidence: 99%